2009
DOI: 10.1086/595688
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Graft‐Site Candidiasis after Kidney Transplantation Is Acquired during Organ Recovery: A Multicenter Study in France

Abstract: Graft-transmitted candidiasis that ends most often in fungal arteritis is associated with high morbidity and mortality after kidney transplantation and is related to organ contamination during recovery in the donor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
115
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(118 citation statements)
references
References 42 publications
(32 reference statements)
1
115
0
1
Order By: Relevance
“…Albano et al reported positive cultures in 8 of 11 arterial specimens, but in only 2 of 11 recipients the blood cultures were positive. 9 Renal arteritis cannot be ruled out in the absence of candidemia or candiduria.…”
Section: 10e19mentioning
confidence: 99%
See 2 more Smart Citations
“…Albano et al reported positive cultures in 8 of 11 arterial specimens, but in only 2 of 11 recipients the blood cultures were positive. 9 Renal arteritis cannot be ruled out in the absence of candidemia or candiduria.…”
Section: 10e19mentioning
confidence: 99%
“…5,8,12,13 Appropriate antifungal prophylactic therapy has not been determined yet, and centers are applying different approaches, ranging from no therapy to therapy with 2 drugs for at least 3 months. 9,13 When a renal artery aneurysm is detected, the end result is almost invariably allograft removal. 6e9,20 In Conclusion, perfusion fluid contamination in our sample occurred in 6 of 70 samples (incidence of 8.6%).…”
Section: 10e19mentioning
confidence: 99%
See 1 more Smart Citation
“…Donor-derived fungal infections are a rare but significant complication in transplant recipients (1)(2)(3). The existence of a transmissible infection in the donor and the risk posed by such transmissions often remains unrecognized at the time of recovery of organs.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical presentation of these patients includes pain and tenderness over the graft site, fever, a progressive decline in renal function, leukocytosis, hematuria, enlarged kidney on ultrasonography with typical radiologic features on contrast-enhanced computerized tomography. 16 Renal papillary involvement may sometimes be seen in transplant patients owing to acute rejection, 6 with fungal infections of the renal allograft including renal candidiasis, 8,17 aspergillosis, 9 cryptococcosis, 18 or histoplasmosis. 19 The association of renal papillary necrosis with renal allograft mucormycosis as seen in our patient is unusual.…”
Section: Discussionmentioning
confidence: 99%